Prediction of Cerebrovascular and Cardiovascular Events in Patients With Subclinical Carotid Atherosclerosis: The Role of C-reactive Protein. (1st January 2008) - Rizzo, Manfredi; Corrado, Egle; Coppola, Giuseppe; Muratori, Ida; Novo, Salvatore
Abstract : Background: Several studies have suggested that inflammation and infection may be important for accelerated progression of atherosclerosis, but few data are available on subjects with early stages of atherosclerosis. Methods and Results: We included, in a prospective 5-year follow-up study, 150 patients with subclinical carotid atherosclerosis, evaluating at baseline all established traditional cardiovascular risk factors (eg, older age, male sex, obesity, hypertension, diabetes, smoking, family history of coronary artery disease, and dyslipidemia); 2 markers of inflammation, fibrinogen, and high-sensitivity C-reactive protein (CRP); and the seropositivity to Helicobacter pylori, Chlamydia pneumoniae, and cytomegalovirus. After follow-up, cardiovascular and cerebrovascular events were registered in the 19% of patients, and the increment in CRP levels (in quintiles) was significantly associated with ischemic stroke ( P = 0.0253), acute myocardial infarction ( P = 0.0055), cardiovascular or cerebrovascular death ( P = 0.0145), and the presence of any event ( P = 0.0064). Most traditional cardiovascular risk factors (eg, older age, hypertension, diabetes, and dyslipidemia) were significantly associated with the events but only in the unadjusted analysis; in fact, at logistic regression analysis, among all baseline variables, only elevated CRP levels showed a predictive role (odds ratio, 7.0; 95% confidence interval, 2.2-18.4; P = 0.0247). Conclusions: Our findings suggest that elevated CRP concentrations may significantly influence the occurrence of cerebrovascular and cardiovascular events in patients with baseline subclinical carotid atherosclerosis. Notably, null findings were obtained by viral and bacteria titers, suggesting a greater role of inflammation (and not of infection) in the progression of atherosclerosis in our cohort. However, further studies are needed to evaluate the therapeutic implications in this category of patients.